As novas imagens do pitoresco: turismo e comodificação da natureza no Parque Nacional dos Lençóis Maranhenses - COSTA, Benedita de Cássia Ferreira (2023)
The Lençóis Maranhenses National Park (PNLM), established as an integral protection conservation unit in 1981, is currently one of the most desired tourist destinations for people from all over the world. Despite its natural attractions, it is a territory marked by tensions, disputes, and socio-environmental conflicts due to the historical presence of families from traditional communities, even before it was established, who traditionally live there and develop their economic activities and others related to tourism. As a tourist destination, the PNLM is constructed by the social imaginary as a place that possesses a paradisiacal, untouched nature, disconnected from human production and, due to these social constructions, it becomes a propitious destination for economic exploitation by agents linked to the tourism chain. In this scenario, the image becomes an instrument of reproduction and perpetuation of such imaginary, helping not only to conform and consolidate the view of nature, but also serving as an effective tool of mediation and seduction of the gaze for the tourist consumption of nature in the PNLM. Anchored in this problematic, the present work pays attention to the process of constitution of images that forge and portray the PNLM as paradise, elaborated by different agents in the process of commodification of nature. Such analytical effort is carried out from some axes of discussion as: the understanding of the notion of commodification of nature and the role of tourism in this process; the historical and anthropological understanding of tourism and its routes through nature, especially in the so-called protected areas, privileging the case of the Lençóis Maranhenses National Park; the problematization of the image that led to the identification of aesthetic films, such as the picturesque and the instagrammable, and its role in the process of manufacturing of the view of nature, which is shaped for tourism consumption in that conservation unit. Based on a qualitative methodology, built in the form of a circuit, it contemplates ethnographic information from fieldwork, carried out in Barreirinhas and Santo Amaro (2019-2022); bibliographic surveys, investigation in secondary sources such as official documents, reports, tourism magazines; research in image repository and social networks, photography books, photo essays; thus, allowing to transit between images, narratives and practices elaborated by several agents (agency owners, guides, attendants, salespeople, tourists, local entrepreneurs, natives) involved with the tourist activity in PNLM. The central issue of this thesis is related to the power that underlies the elaboration of images that crystallize the nature of the PNLM, which resides in the updating of the picturesque and in the incorporation of new aesthetics, such as Instagram, being able not only to convince the eye, mediating the decisions of nature consumption through tourism, but also to invisibilize the existence of traditional populations that live there, from frames that highlight nature as a scenario, composed only by white and winding dunes and lagoons with crystal clear waters under a blue summer sky.